MATERIAIS ELETROATIVOS BASEADOS EM HIDRÓXIDO DE NÍQUEL APLICADOS A ELETROCATÁLISE - Nunes Júnior, Cicero Venâncio (2013)
This work aimed to study the α - Ni(OH)2 phase stability, intercalated in bentonite clay (BNi), a material synthesized in 2004, verifying its structural, thermal and electrochemical behavior after these years. On grounds of comparison, other material was synthesized using the additive cobalt (NiCo) in various proportions - 90:10, 80:20, 60:40, 50:50, 40:60, 20:80. BNi is stable in the phase α - Ni(OH)2 even after these years. This is clear in its structural, thermal and electrochemistry analysis. For characterization BNi was dried at room temperature and by freeze drying. The diffractograms show peaks of reflection characteristic of the material interspersed with clay. The lyophilized material has a higher basal spacing in the reflection peak (001), thus favoring a better diffusion process between the involved species. This is evidenced by the lyophilized material behavior (BNi-Lyo), which shows more reversible electrochemical behavior. When its morphology is compared, the BNi-Lyo is more porous compared to the BNi dried at room temperature. The NiCo, in its various proportions, were studied and their compositions were close to the experimental when studied by EDXRF. The NiCo stabilizes the phase α - Ni(OH)2. Among the proportions, the one that shows better answer is NiCo 60:40, which through its diffractogram presents greater basal spacing to reflection the plane (003). Checking the electrochemical behavior, cobalt promotes the redox displacement of the nickel hydroxide to potential cathode, fleeing the evolution of oxygen and moving away from the phase α potential. Both materials showed good responses in the catalysis of alcohols (methanol, ethanol, glycerol).